Gene Regulatory Pathways Associated with Maintenance of Acrosomal Integrity in Bovine Sperm - Swathi, Divakar; Ramya, Laxman; Lavanya, Maharajan; Archana, Santhanahalli Siddalingappa; Krishnappa, Balaganur; Binsila, B Krishnan; Selvaraju, Sellappan (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The objective of this study was to identify the sperm-expressed genes and their pathways in maintaining acrosomal integrity for elucidating the regulatory genes involved in determining bull fertility. Semen samples collected from Holstein-Friesian bulls (n=12) were analyzed for acrosomal integrity and were grouped into high acrosomal integrity (n=6) and low acrosomal integrity (n=6). In these sperm samples, total RNA was isolated and subjected to whole transcriptome profiling using Illumina platform. Bioinformatic analyses led to the identification of 1601 up-regulated (TMCO2, GTSF1, SWI5, CCDC174 and CABS1) and 567 down-regulated (MYCB, RPS21 and PPIA) genes. The study also validated the expression levels of CCDC174 and TMCO2 using real-time PCR. The pathways [log2 (p-value)] such as spermatid development (12.17), protein transport (9.57) and mitochondrial electron transport (10.20) were enriched in the up-regulated genes. These identified pathways and their associated transcripts in high acrosome integrity group suggest that these pathways are essential for maintaining acrosome integrity and sperm fertility in bulls.